ROLE OF ANTENATAL ULTRASONOGRAPHY IN THE DETECTION OF FETAL CONGENITAL ANOMALIES: A HOSPITAL BASED OBSERVATIONAL STUDY AT A TERTIARY CARE CENTRE IN ASSAM, INDIA (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Globally, congenital fetal malformations are the leading cause of perinatal morbidity and mortality. Prenatal ultrasound has become a clinically recognized first-line early non-invasive screening tool. This study was conducted at a tertiary care hospital in Assam, India, and used ultrasound screening to assess the type spectrum and prevalence of fetal malformations. Objective: This study, a project of prenatal ultrasound screening for fetal congenital anomalies, was conducted at the Radiology Department of FAAMCH Hospital in Barpeta, Assam, India. Methods: The paper opens with a clear statement of two core research objectives, outlines the implementation details of the entire research workflow, and adopts SPSS in conjunction with descriptive statistical analysis. All study parameters are explicitly documented, which enables the replication and traceability of the research, and aligns with the standard writing logic of medical scientific research papers. Results: Baseline statistics of congenital fetal anomalies in the cohort of this study show that central nervous system anomalies rank first at 37.5%, followed by cardiovascular anomalies at 17.5%, gastrointestinal anomalies at 15%, and other types. Anencephaly accounts for 12.5% of all cases, lethal anomalies account for 25%, live births make up 52.5% of all pregnancy outcomes, and 20% of the cases are associated with maternal diabetes. Conclusion: Antenatal ultrasonography remains indispensable in the early detection and characterization of fetal congenital anomalies, with CNS malformations predominating in the study population. Early and systematic anomaly scanning facilitates timely counseling, informed obstetric decision-making, and improved perinatal outcomes.